Abundance patterns of Anopheles pseudopunctpennis and Anopheles argyritarsis in northwestern Argentina - Dantur Juri, Maria Julia (2010)
Anopheles pseudopunctipennis is an important malaria vector in Argentina but the role of Anopheles argyritarsis in the transmission of the parasite is still unknown. Abundance patterns of both species and their relationship to climatic variables were studied in the subtropical mountainous forest in northwestern Argentina. Adults were collected with CDC light traps from September 2002 to November 2005 in Salta (northern area) and Tucumán (southern area) provinces, from 3 localities in each province. The abundance of both species in localities was compared using the Kruskal–Wallis test, and their changes in abundance in relation to climatic variables were analyzed by Multilevel Poisson Regression. Anopheles argyritarsis was more abundant than A. pseudopunctipennis, and both reached a peak during the spring. There were significant differences in abundance in the northern localities for A. pseudopunctipennis, and between northern and southern localities for A. argyritarsis. Temperature, rainfall and relative humidity were significant predictors of the abundance of these two species.